Glycopolypeptide-grafted bioactive polyionic complex vesicles (PICsomes) and their specific polyvalent interactions - Pandey, Bhawana; Mahato, Jaladhar; Cotta, Karishma Berta; Das, Soumen; Sharma, Dharmendar Kumar; Sen Gupta, Sayam; Chowdhury, Arindam (ACS Omega, 2016)
Glycopolypeptide-based self-assembled nano-/microstructures with surface-tethered carbohydrates are excellent mimics of glycoproteins on the cell surface. To expand the broad repertoire of glycopolypeptide-based supramolecular soft structures such as polymersomes formed via self-assembly of amphiphilic polymers, we have developed a new class of polyionic complex vesicles (PICsomes) with glycopolypeptides grafted on the external surface. Oppositely charged hydrophilic block copolymers of glycopolypeptide(20)-b-poly-L-lysine(100) and PEG(2k)-b-poly-L-glutamate(100) [PEG = poly(ethylene glycol)] were synthesized using a combination of ring-opening polymerization of N-carboxyanhydrides and ``click'' chemistry. Under physiological conditions, the catiomer and aniomer self-assemble to form glycopolypeptide-conjugated PICsomes (GP-PICsomes) of micrometer dimensions. Electron and atomic force microscopy suggests a hollow morphology of the PICsomes, with inner aqueous pool (core) and peripheral PIC (shell) regions. Owing to their relatively large (similar to micrometers) size, the hollowness of the supramolecular structure could be established via fluorescence microscopy of single GP-PICsomes, both in solution and under dry conditions, using spatially distributed fluorescent probes. Furthermore, the dynamics of single PICsomes in solution could be imaged in real time, which also allowed us to test for multivalent interactions between PICsomes mediated by a carbohydrate (mannose)-binding protein (lectin, Con-A). The immediate association of several GP-PICsomes in the presence of Con-A and their eventual aggregation to form large insoluble aggregate clusters reveal that upon self-assembly carbohydrate moieties protrude on the outer surface which retains their biochemical activity. Challenge experiments with excess mannose reveal fast deaggregation of GP-PICsomes as opposed to that in the presence of excess galactose, which further establishes the specificity of lectin-mediated polyvalent interactions of the GP-PICsomes.